Peningkatan Kemampuan Sitasi Mahasiswa melalui Pelatihan Mendeley di Fakultas Ekonomi dan Bisnis Universitas Pattimura - Zahra Zahra; Wiljan Atfentia Kotngoran; Yerimias Manuhutu; Desry J. Louhenapessy; Ummi Duwila (Yayasan Literasi Sains Indonesia, 2026)
This community service activity aimed to enhance the citation skills of students from the Faculty of Economics and Business (FEB) at Pattimura University through training on using the Mendeley application. The primary identified problem was the students' lack of knowledge and skills in properly compiling citations and bibliographies, which potentially led to inconsistent formatting, writing errors, and unintentional plagiarism. The training was conducted in three structured stages: preparation, implementation, and evaluation. The preparation stage involved problem identification, participant registration, and material preparation. The implementation consisted of delivering theoretical material, hands-on practice using Mendeley, and responsive direct mentoring. Evaluation was carried out through a Q&A session and an online feedback form. The results demonstrated that the training successfully increased participants' understanding of Mendeley's functions and benefits. Participant enthusiasm, indicated by the number of registrants exceeding the quota, reflected a genuine need for reference management literacy. This activity not only provided technical skills but also raised awareness of the importance of correct and ethical citation in scientific writing. It is hoped that this training can serve as an initial step in fostering an academic culture of integrity and supporting the improvement of the quality and productivity of scientific works by FEB students at Pattimura University.